(untitled) (Journal of the College of Basic Education, 2025)
The current research aims to identify the effect of using the P.R.O.R. strategy on developing probing thinking among students in the Department of Art Education, Art Psychology. The researcher formulated two null hypotheses: 1. There are no statistically significant differences at the (0.05) level between the average scores of the experimental group and the average scores of the control group on the post-test cognitive achievement test in Art Psychology. .2There are no statistically significant differences at the (0.05) level between the average scores of the experimental group and the average scores of the control group on the post-test probing thinking scale. The researcher used the experimental method and the experimental design with two equivalent groups, experimental and control, was used. The total research sample was (60) male and female students, (30) male and female students represented the experimental group, and (30) male and female students represented the control group. The researcher prepared the research tool represented by the achievement test consisting of (20) items from a multiple-choice test, which was characterized by validity and reliability, in addition to constructing a scale for probing thinking, which was also characterized by validity and reliability. The experiment continued for (6) weeks. After applying the tool and using statistical methods in processing the data, the results showed the presence of statistically significant differences at a significance level of (0.05) between the average ranks of the scores of the students of the experimental group who studied according to (P.R.O.R. strategy) and the average scores of the students of the control group who studied according to (the traditional method) regarding their answers to the achievement test and the probing thinking scale afterward, in favor of the experimental group. This indicates that the curriculum based on the P.R.O.R. strategy had an impact on enhancing the development of critical thinking among students in the experimental group